2013
DOI: 10.1099/ijs.0.039198-0
|View full text |Cite
|
Sign up to set email alerts
|

Loktanella litorea sp. nov., isolated from seawater

Abstract: A Gram-negative, non-motile, rod-shaped bacterial strain, designated DPG-5 T , was isolated from seawater of the South Sea, Korea and subjected to a study using a polyphasic taxonomic approach. Strain DPG-5 T grew optimally at pH 7.0-8.0, at 30 6C and in the presence of 2 % (w/ v) NaCl. Neighbour-joining phylogenetic analyses based on 16S rRNA gene sequences revealed that strain DPG-5 T fell within the clade comprising members of the genus Loktanella, and formed a cluster with the type strains of Loktanella ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…The cellular fatty acid profile of strain D1-W3 T consisted of C 18 : 1 v7c (69.3 %), C 16 : 0 (13.6 %), C 18 : 0 (8.2 %), C 12 : 1 3-OH (5.8 %) and C 10 : 0 3-OH (3.0 %). The fatty acid profile of strain D1-W3 T was similar to those of species of the genus Loktanella in that the predominant Yoon et al (2013) unless otherwise indicated and data for column 4 taken from this study unless otherwise indicated. All strains were positive for catalaseD and oxidaseD activities; utilization of cellobiose, D-fructose (weak for L. rosea LMG 22534 T ), D-galactose, D-glucose, D-xylose, acetate and L-malate (weak for strain D1-W3 T ); susceptibility to ampicillin, carbenicillin, cephalothin, chloramphenicol, gentamicin, neomycin, novobiocin, oleandomycin, penicillin G, tetracycline (weak for L. rosea LMG 22534 T ) and streptomycin; and activity of alkaline phosphatase, esterase (C4) and esterase lipase (C8).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The cellular fatty acid profile of strain D1-W3 T consisted of C 18 : 1 v7c (69.3 %), C 16 : 0 (13.6 %), C 18 : 0 (8.2 %), C 12 : 1 3-OH (5.8 %) and C 10 : 0 3-OH (3.0 %). The fatty acid profile of strain D1-W3 T was similar to those of species of the genus Loktanella in that the predominant Yoon et al (2013) unless otherwise indicated and data for column 4 taken from this study unless otherwise indicated. All strains were positive for catalaseD and oxidaseD activities; utilization of cellobiose, D-fructose (weak for L. rosea LMG 22534 T ), D-galactose, D-glucose, D-xylose, acetate and L-malate (weak for strain D1-W3 T ); susceptibility to ampicillin, carbenicillin, cephalothin, chloramphenicol, gentamicin, neomycin, novobiocin, oleandomycin, penicillin G, tetracycline (weak for L. rosea LMG 22534 T ) and streptomycin; and activity of alkaline phosphatase, esterase (C4) and esterase lipase (C8).…”
mentioning
confidence: 94%
“…At the time of writing, the genus Loktanella comprised 13 species with validly published names: Loktanella salsilacus, L. fryxellensis and L. vestfoldensis (Van Trappen et al, 2004), L. hongkongensis (Lau et al, 2004), L. agnita and L. rosea (Ivanova et al, 2005), L. koreensis (Weon et al, 2006), L. maricola (Yoon et al, 2007), L. atrilutea (Hosoya & Yokota, 2007), L. pyoseonensis (Moon et al, 2010), L. tamlensis (Lee, 2012), L. litorea (Yoon et al, 2013) and L. cinnabarina (Tsubouchi et al, 2013). Members of the genus Loktanella have been isolated from Antarctic lakes and marine environments (Van Trappen et al, 2004;Lau et al, 2004;Ivanova et al, 2005;Weon et al, 2006;Yoon et al, 2007;Hosoya & Yokota, 2007;Moon et al, 2010;Lee, 2012).…”
mentioning
confidence: 99%
“…agnita (Ivanova et al, 2005), L. sediminilitoris KCTC 32383 T (Park et al, 2013a) and L. cinnabarina (Tsubouchi et al, 2013), and bacteria not containing PE in their polar lipid profiles, L. pyoseonensis (Moon et al, 2010), L. hongkongensis (Tsubouchi et al, 2013) and L. soesokkakensis (Park et al, 2013b). At the same time, Yoon et al (2013) reported the presence of PE in L. salsilacus whereas PE was not found in this bacterium in the study of Tsubouchi et al (2013). Tsubouchi et al (2013) and Park et al (2013b) reported that the same L. cinnabarina cluster includes bacteria containing PE (L. cinnabarina itself) and bacteria without PE (L. pyoseonensis, L. hongkongensis and L. soesokkakensis).…”
Section: Ketogulonicigenium Vulgare Dsm 4025 T (Af136849)mentioning
confidence: 99%
“…The genus Loktanella was expanded to include twelve more species, including Loktanella hongkongensis (Lau et al, 2004), L. agnita, L. rosea (Ivanova et al, 2005), L. koreensis (Weon et al, 2006), L. atrilutea (Hosoya & Yokota, 2007), L. maricola (Yoon et al, 2007), L. pyoseonensis (Moon et al, 2010), L. tamlensis (Lee, 2012), L. cinnabarina (Tsubouchi et al, 2013), L. litorea (Yoon et al, 2013), L. sediminilitoris (Park et al, 2013a) and L. soesokkakensis (Park et al, 2013b). Here we report the polyphasic characterization of a Gramstain-negative, aerobic, beige-pigmented, non-motile bacterium, designated KMM 9530 T , which was isolated from a shallow sediment sample.…”
mentioning
confidence: 99%
“…S3). The type strain of L. salsilacus (the type species of the genus) was reported to have major amounts of phosphatidylcholine and phosphatidylglycerol and a minor amount of phosphatidylethanolamine (Yoon et al, 2013a). The type strain of L. soesokkakensis, the closest phylogenetic relative, was described to have phosphatidylcholine, phosphatidylglycerol, diphosphatidylglycerol, one unidentified glycolipid and one unidentified aminolipid .…”
mentioning
confidence: 99%